PRINCIPLES OF ENSURING SAFETY IN THE EVENT OF A RADIATION ACCIDENT USING THE "CONSIDER ALL FACTORS! (CAF)" METHOD. EFFECTIVENESS OF TEACHING THE TOPIC "IMPLEMENTATION OF DEACTIVATION WORKS" - Mukhlisakhon Abdullayeva (Zeta Repository, 2023)
The idea, and practical value of any activity, process and system depends on what principles it is based on. For this reason, priority principles, which take a leading place in its essence, are determined in planning the organization of activities, ensuring the flow of the process and forming the system. Therefore, in the article, consider all factors in the teaching of Industrial and radiation safety in higher education institutions! Using the "Consider all factors! (CAF)" method, a lesson was organized and suggestions for its use were made and a pedagogical analysis was made.